2006
DOI: 10.1021/bi0619268
|View full text |Cite
|
Sign up to set email alerts
|

Microsomal Triglyceride Transfer Protein Is Required for Yolk Lipid Utilization and Absorption of Dietary Lipids in Zebrafish Larvae

Abstract: Although the absorption, transport, and catabolism of dietary lipids have been studied extensively in great detail in mammals and other vertebrates, a tractable genetic system for identifying novel genes involved in these physiologic processes is not available. To establish such a model, we monitored neutral lipid by staining fixed zebrafish larvae with oil red o (ORO). The head structures, heart, vasculature, and swim bladder stained with ORO until the yolk was consumed 6 days after fertilization (6 dpf). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
144
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(150 citation statements)
references
References 42 publications
6
144
0
Order By: Relevance
“…To investigate whether yolk lipid transportation and utilization are affected in CagApo-14 morphants, we monitored neutral fat by staining the fixed larvae with Oil Red O (ORO) (Schlegel and Stainier, 2006). In wild-type embryos at 36 hpf, staining of yolk lipid was found in vasculature (Fig.…”
Section: Defection Of Yolk Lipid Transportation In Vasculature Of Cagmentioning
confidence: 99%
“…To investigate whether yolk lipid transportation and utilization are affected in CagApo-14 morphants, we monitored neutral fat by staining the fixed larvae with Oil Red O (ORO) (Schlegel and Stainier, 2006). In wild-type embryos at 36 hpf, staining of yolk lipid was found in vasculature (Fig.…”
Section: Defection Of Yolk Lipid Transportation In Vasculature Of Cagmentioning
confidence: 99%
“…The intravascular lipids of embryonic zebrafish are dyed by Oil Red O. Schlegel and Stainier (13) reported that the vasculature of zebrafish no longer had stainable neutral lipids six days post fertilization (dpf). Therefore, the changes in intravascular lipids among 1-8-dpf zebrafish were observed using Oil Red O staining in the present study.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the large number of putative candidate genes identifi ed, the functions of many remain largely unknown, owing in part to the lack of physiologically relevant in vivo models with which to validate and characterize the functionality of associated variants ( 3, 4, 6-13 ). Development of novel models in which genes can be individually targeted will likely reveal functional roles for genetic determinants of blood lipid levels and may facilitate discovery of novel targets for drug development.The zebrafi sh is an excellent candidate for establishing genetic models of hyperlipidemia due to conservation of cell types and molecular pathways involved in lipid metabolism and cholesterol synthesis ( 8,(14)(15)(16)(17)(18)(19)(20). These include hepatocytes, adipocytes, and pancreatic acinar cells ( 17 ) as well as expression of genes involved in lipid transport and metabolism, such as LDL receptor ( ldlr ), sterol regulatory element binding protein ( srebp ) 1/2 , and HMG-CoA reductase ( Hmgcr ) ( 18-29 ).…”
mentioning
confidence: 99%